COVID-19 Preparedness and Response by Global South and Global North Countries: A Comparative Analysis (2022)
Comparing the countries’ level of preparedness and response to the Covid-19 pandemic involves the assessment of human development, health, connectivity and death rate indicators. In this study, information published by the United Nations Development Program (UNDP) and the World Health Organization (WHO) was used to assess the performance of 148 countries classified as either of the Global South (Africa, Latin America and Asia-Oceania) or the Global North, describing how the unequal social and health conditions between regions are reflected in terms of contagion and death figures at year-end 2020. The HJ-Biplot multivariate technique was used to simultaneously represent both the countries and the indicators, providing a descriptive and exploratory analysis of how the countries’ level of preparedness to face the pandemic in terms of health and human development did not determine their success in reducing Covid-19 contagion and death rates, because success also depends on efficient and quick government action and reaction strategies. © 2022 Universidad Nacional de Colombia. All rights reserved.